Analysis of surface plasmon resonance biosensors for protein detection - Faruque, Abdullah Al; Maoya, Jannatul; Bisher, Kazi Diganta (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.